Breast Cancer: A Lifestyle Medicine Approach. Issue 5 (September 2020) - Orman, Amber; Johnson, Dianne L.; Comander, Amy; Brockton, Nigel
Breast cancer is the most common female cancer diagnosis in the United States (excluding skin cancers), and the second leading cause of female cancer death. This article highlights the role that lifestyle plays in primary breast cancer prevention, breast cancer treatment, and tertiary breast cancer prevention. Current data regarding the benefits of a predominantly plant-based diet in combination with physical activity and maintenance of a healthy body weight will be reviewed. The evidenced-based patient-focused recommendations developed by the World Cancer Research Fund/American Institute for Cancer Research will be discussed in the context of an overall lifestyle strategy. It is our hope that this publication empowers clinicians to provide patients with personalized cancer-protective lifestyle prescriptions.